Pemanfaatan Aplikasi Quizizz dalam Evaluasi Mata Pembelajaran Geografi di Sekolah - Marlina, Marlina; Nyompa, Sukri; Muntazarah, Fediyatun (LaGeografia, 2025)
The evaluation of geography learning can be made more engaging through the use of applications. Utilizing the Quizizz application as an evaluation tool in school-based geography instruction is important, as it serves as an online assessment platform that offers an interactive and enjoyable approach for students to measure their understanding. This study employs a qualitative descriptive method and literature review to explore how to design an application-based evaluation model aimed at enhancing student motivation and learning outcomes. The findings indicate that the use of Quizizz increases student engagement, accelerates the evaluation process, and provides instant feedback. Features such as avatars, themes, and gamification elements like points and leaderboards create a competitive environment that encourages active participation. Moreover, Quizizz supports collaborative geography learning by allowing students to assist each other in comprehending the material. The results demonstrate that this application not only facilitates teachers in conducting assessments but also helps students adapt to digital technology, making it a highly recommended tool in modern education, especially for improving learning outcomes and student interest in geography through engaging features, including visualizations of geospheric phenomena.AbstrakEvaluasi pembelaharan geografi akan lebih menarik dengan pengunaan aplikasi. Pemanfaatan aplikasi Quizizz sebagai alat evaluasi dalam pembelajaran geografi di sekolah penting untuk sebagai platform evaluasi berbasis online, menawarkan pendekatan interaktif dan menyenangkan bagi siswa untuk mengukur pemahaman mereka. Penelitian ini menggunakan metode deskriptif kualitatif dan studi literatur untuk mengeksplorasi bagaimana merancang model evaluasi berbasis palikasi untuk meningkatkan motivasi dan hasil belajar siswa. Hasil penelitian menunjukkan bahwa penggunaan Quizizz dapat meningkatkan keterlibatan siswa, mempercepat proses evaluasi, dan memberikan umpan balik langsung. Fitur-fitur menarik seperti avatar, tema, dan elemen gamifikasi seperti poin dan papan skor menciptakan suasana kompetitif yang mendorong partisipasi aktif. Selain itu, Quizizz mendukung pembelajaran geografi yang kolaboratif, memungkinkan siswa untuk saling membantu dalam memahami materi. Temuan menunjukkan bahwa aplikasi ini tidak hanya mempermudah guru dalam evaluasi, tetapi juga membantu siswa beradaptasi dengan teknologi digital, menjadikannya alat yang sangat direkomendasikan dalam pendidikan modern, terutama dalam meningkatkan hasil belajar dan minat siswa dalam mata pelajaran geografi dengan berbagai fitur menarik termaksud fitur fenomena geosfer yang ditampilkan.